Arcus Venosus Dorsalis Pedis Graft to Restore the Superficial Palmar Arch in Devascularized Hands - Liu, Shen; Liu, Jun-Jian; Liu, Sheng-He; Cai, Zheng-Dong; Chung, Kevin; Fan, Cun-Yi (Journal of Reconstructive Microsurgery, 2012)
For complex amputation injuries and anatomical characteristic of the metacarpus, restoration to the superficial palmar arch in severe devascularized or amputated hands remains a daunting challenge. In this article, we treated a series of five cases using an arcus venosus dorsalis pedis (AVDP) graft to restore the superficial palmar arches in devascularized hands. All hands survived and satisfying function was gained. The AVDP graft may be a suitable option to restore the superficial palmar arch in devascularized hands.
Keywords: arcus venosus dorsalis pedis; devascularized hand; superficial palmar arch